Desert Rose‐Shaped Zircon Synthesized by Low‐Temperature Hydrothermolysis. Issue 5 (22nd January 2015) - Lei, Binglong; Qin, Wu; Kang, Guiluan; Peng, Cheng; Wu, Jianqing
Abstract : This study has presented synthesis, characterization, and formation mechanism of a kind of novel porous zircon with desert rose‐shaped morphology, which was hydrothermally fabricated by a two‐step quasi‐ in situ reaction in a system of silica hydrogel and well‐dispersed ZrO2 precursor microspheres. The micro–mesoporous zircon product possesses a sole crystalline phase of hydroxyl‐fluorinated ZrSiO4 without unreacted ZrO2 or SiO2 in the final resultant. It has a specific surface area exceeding 120 m 2 /g and can maintain more than 50% micro‐mesoporic pores after calcination at 800°C due to its magnificent thermal stability. A four‐stage formation mechanism has been proposed to elucidate the process of quasi‐ in situ crystallization and growth for the rose‐shaped zircon.